Permohonan Izin Poligami pada Pengadilan Agama Surabaya: (Studi Putusan Nomor 1751/Pdt.G/2024/PA.Sby) - Diniati Wafida Rohmah; Murni Murni (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
The aim of this inquiry is to excavate a profound comprehension concerning the quest for a polygamy license, by delving into the judicial decree regarding the rationale of the Surabaya Religious Tribunal in bestowing such a license, scrutinizing and dissecting the juridical and communal dimensions of ruling number 1751/Pdt.G/2024/PA. Sby. Here, the Seeker sought approval for polygamy against the Opponent due to the Opponent’s incapacity to satisfy the Seeker’s carnal desires, attributed to the presence of diabetes. The quandaries investigated pertain to the statutes and stipulations governing polygamy petitions and the Jurist’s rationale in adjudicating the polygamy license request. This investigation employs a normative jurisprudence technique, drawing upon an examination of texts, and adopts a legislative framework in its approach. The findings of this examination indicate that the Panel of Jurists factors in both legal and compassionate facets in its deliberations.